2019
DOI: 10.3390/ijms20153738
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cells in Homeostasis and Systemic Diseases: Hypothesis, Evidences, and Therapeutic Opportunities

Abstract: Mesenchymal stem cells (MSCs) are present in all organs and tissues, playing a well-known function in tissue regeneration. However, there is also evidence indicating a broader role of MSCs in tissue homeostasis. In vivo studies have shown MSC paracrine mechanisms displaying proliferative, immunoregulatory, anti-oxidative, or angiogenic activity. In addition, recent studies also demonstrate that depletion and/or dysfunction of MSCs are associated with several systemic diseases, such as lupus, diabetes, psoriasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
85
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(89 citation statements)
references
References 163 publications
0
85
0
4
Order By: Relevance
“…Several experiments revealed that MSCs exhibited a different restorative capacity based on isolation from various tissues. Also, the MSC subtype possesses a different multipotential capacity [59]. Bone marrow is a primary and well-known source for the isolation of MSCs.…”
Section: Application Of Mscs In Asthmamentioning
confidence: 99%
“…Several experiments revealed that MSCs exhibited a different restorative capacity based on isolation from various tissues. Also, the MSC subtype possesses a different multipotential capacity [59]. Bone marrow is a primary and well-known source for the isolation of MSCs.…”
Section: Application Of Mscs In Asthmamentioning
confidence: 99%
“…Stem cells, although in minimal quantities, are present in many tissues of the body including the lungs, and participate and control tissue renewal. Furthermore, there is a subtype of stem cells, relatively unknown until recently, called mesenchymal (stem) stromal cells (MSC), which are active sentinels and regulators in tissue homeostasis (Vizoso et al, 2019). In fact, it has been proposed that in many degenerative, autoimmune diseases (such as lupus, rheumatoid arthritis, psoriasis, etc.…”
Section: Mesenchymal Stromal Cellsmentioning
confidence: 99%
“…Due to the moderate efficacy of MSC applications in the first clinical trials, research was carried out toward cellular modifications of MSC in order to improve their biological effect, such as genetic modifications, MSC preconditioning, pharmacologic modulation, or the combined application of MSC together with pharmacologic therapies (Vizoso et al, 2019). However, there is a growing trend in the scientific community to recognize that the beneficial therapeutic effect of MSC relies on the cocktail of substances that clump together under the generic term of secretome (growth factors, cytokines, or extracellular vesicles).…”
Section: Msc Secretome As New Therapeutic Strategies In Lung Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Pathological conditions may alter the microenvironment surrounding MSCs a d impair their functions. Some findings have demonstrated that MSC dysfunctions are associated with several diseases, including diabetes, lupus, psoriasis, rheumatoid arthritis, and metabolic syndrome [8,9].…”
Section: Introductionmentioning
confidence: 99%